A proposal of indicators to promote happiness in the classroom in higher education: a focus of professors’ opinions - Cerdá Suárez, Luis Manuel (INTED Proceedings, 2020)
Despite the widespread growth of interest in the analysis of academic programs and syllabuses in Europe and America, the behavior of professors and students is very different among several regions. From a local territorial perspective, the analysis of the professors' motivations in the context of happiness in the classroom provides a relevant vision to characterize this non-homogeneous spatial distribution, and it is a relevant perspective in order to promote this type of teaching in the classroom. The objectives of this work are the following: 1) to conceptualize the satisfaction and happiness at universities as a set of attributes providing positive emotions in the classroom; and 2) to evidence empirically the factors for success of these behaviors in several institutions of the Spanish and Mexican geographies. The methodology of this research presents a bibliographic review of those constructs and several in-depth interviews were applied to a diverse sample of professors, in terms of their perceptions related to the best way to implement their practices in the classroom. This study reinforces the importance to manage several factors for success in the classroom and presents a proposal of indicators to promote happiness and satisfaction to different levels of management.
Ponencia de la conferencia: "13th International Technology, Education and Development Conference (INTED)", Valencia, Spain.
Keywords: teaching style; learning; happiness; classroom; higher education; WOS(2)